Manajemen Usaha Peternakan Ayam Petelur dengan Penerapan Sistem Informasi Manajemen - Endy Suwondo (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2001)
The efficiency of a company will be determined by effectiveness of management on production resources. So, implementing a managemwntinformation system with ability to process the transaction, analysis, and planning will increase the benefit to a layer poultry farm for more easy management. By identifying the production factors and through a need assessment of a layer poultry farm company, it could be determined the elements of information needed for storage, for processing (information transformation), and for generating report. To achieve the goal, the process for system design was carried out on structured and iterative principle until an ideal design derived. Development of the software with a modular technique on a text-based operating system allows the end user to operate it on a through development of data flow diagram and prototyping lead to produce a user-friendly application. The relationship between elements of information them created base on closeness and frequently access of information to get an efficient data base with quick respond on information call, effective information processing, and a minimum data storage. Therefore, the system will be interactive, fast, and easy to use. Through a series of review and test, the system developed show the ability to store and retrieve the data including the capability to display the data history for use on ferecasting. The transaction menu that easy to understand offers all aspect of transaction as well as purchasing and marketing of the product. The transaction process will automatically update the stock data of the product, and can be use to generate a report needed. Therefore, it can be concluded that the implementation of the system will assist the entrepreneur of a layer poultry farm with a minimum of cost for investment.